Ethnomathematics Pada Ornamen Rumah Gadang Minangkabau - Fitriza, Rozi (Math Educa Journal, 2018)
The mathematical concept on cultural objects is one of the objects of study in the study of ethnomathematics. This study aims to uncover mathematical concepts in the ornaments found in the rumah gadang and the development of ornaments. This qualitative research uses participatory observation techniques and documentation to obtain data. The results showed that there were geometrical concepts in the ornaments and the development of the rumah gadang ornaments. The concepts of geometry seen in ornaments include the use of two-dimensional such as square, rectangular, rhombic, circle, ellipse and polygons. Two-dimensional shape are also arranged using certain patterns. The development of ornament forms is carried out using the principles of congruence, tessellation, symmetry patterns and geometric transformations (translation, reflection, rotation, and dilation). The results of this study can be used as a reference for teachers in mathematics learning and ethnomathematics research on cultural objects.Keywords: ethnomathematics, ornaments of rumah gadang